Integration of treasury single account into the accounting education curriculum of colleges of education in Ebonyi and Enugu States of Nigeria - Okorie, Ogbonnaya; Nwokike, Felicia O (American Journal of Education and Learning, 2025)
The main purpose of the study was to determine the extent of integration of TSA and its implications in the accounting education curriculum of colleges of education in Ebonyi and Enugu States for accounting teachers. The researchers adopted a survey research design. Two research questions and two null hypotheses were utilized for the study. Forty-three accounting teachers in the colleges of education in the two states constituted both the population and the sample for the study. Data were collected from the respondents using a four-point ordered questionnaire with a reliability coefficient of 0.72. The hypotheses were tested using a t-test while the research questions were answered using means and standard deviation. The two null hypotheses were tested at the 0.05 level of significance. The study found that the extent of integration of TSA into the accounting education curriculum of colleges of education is low that integration of TSA into the business education curriculum will create a knowledge gap which will demand the retraining of the accounting teachers to implement the curriculum. There is no significant difference between the mean responses of male and female accounting teachers on the extent of the implications of and challenges to the integration of TSA into the accounting education curriculum of colleges of education in Ebonyi and Enugu states of Nigeria. The researchers concluded that the extent of integration of the Treasury Single Account (TSA) into the accounting education curriculum of colleges of education in Ebonyi and Enugu states is low because TSA has not been made a part of the curriculum and accounting teachers have not been trained in the principles of TSA. Integration of the TSA into accounting education curriculum implies that accounting teachers must be trained on the principles and practices of TSA.